A method for preparing a high-performance modified fiber composite material for the fashion industry

CN122896531APending Publication Date: 2026-10-13SUZHOU YINGYU TEXTILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611375470.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]有鉴于此,本发明的目的在于提出一种时装产业用高性能改性纤维复合材料的制备方法,以解决现有技术中多层复合材料无法兼顾保形、差异化补强、环保可降解且保持时装级手感的问题

Benefits of technology

[0037]1、本发明通过将涤纶长丝经常压低温等离子体活化处理,并结合热塑性聚氨酯与低熔点共聚酯共挤皮层,在无需外加粘合剂的条件下实现了基布纤维与皮层材料的高效界面键合,显著提升了复合材料的层间剥离强度,同时避免有机溶剂残留,满足时装贴身穿着的安全环保要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of garment materials, in particular to a preparation method of a high-performance modified fiber composite material for the fashion industry, and specific steps of the preparation method are as follows: step S1, pre-combining a base cloth and a lining; and step S2, hot pasting of a mesh cloth in sections; the application is characterized in that: the polyester filament is activated by normal-pressure low-temperature plasma, and is co-extruded with a thermoplastic polyurethane and a low-melting-point copolyester skin layer; a biomass lining is constructed by extracting keratin from waste feathers and grafting modified lyocell fibers; super-high-strength polyethylene filaments and nylon 6 mesh cloth strips are prepared by adopting a untwisting wrapping process, and are subjected to directional impregnation and intermittent hot pressing and pasting; the three functions of shape retention of a surface layer, ecological stiffening of a lining layer and local toughening of a stress part are realized by using a full-water emulsion system and a solvent-free hot rolling-hot pressing integrated process; and the obtained composite material has the comprehensive performances of high peeling strength, differentiated reinforcement, degradability, skin friendliness and fashion-grade hand feeling, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of clothing materials, and more particularly to a method for preparing a high-performance modified fiber composite material for the fashion industry. Background Technology

[0002] As the fashion industry evolves towards high-end, functional, and environmentally friendly directions, single-fiber materials can no longer meet the complex requirements of shape retention, structural support, and localized reinforcement in designs. Traditional fashion fabrics often use chemical coatings or hot-melt padding to achieve a stiff effect. These methods often sacrifice hand feel and breathability, and the bonding between the functional layer and the surface layer is insufficient, making them prone to delamination, bubbling, or localized failure after repeated wear and washing.

[0003] To address these issues, existing technologies attempt to laminate multiple layers of materials using adhesives. However, the introduction of adhesives often results in residual organic solvents and formaldehyde release, making it difficult to meet the safety and comfort standards required for clothing worn close to the skin. Furthermore, homogeneous adhesive layers cause reinforced and unreinforced areas to have the same stiffness, making it impossible to specifically reinforce stress-bearing areas such as shoulders and plackets while maintaining overall softness and drape. This leads to a trade-off between garment structural stability and wearing comfort.

[0004] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop a method for preparing high-performance modified fiber composite materials for the fashion industry. Summary of the Invention

[0005] In view of this, the purpose of this invention is to propose a method for preparing high-performance modified fiber composite materials for the fashion industry, so as to solve the problem that existing multilayer composite materials cannot simultaneously achieve shape preservation, differentiated reinforcement, environmental degradability, and maintain fashion-grade feel.

[0006] To achieve the above objectives, the present invention provides a method for preparing high-performance modified fiber composite materials for the fashion industry.

[0007] A method for preparing a high-performance modified fiber composite material for the fashion industry, the specific steps of which are as follows:

[0008] Step S1: The base fabric and the lining are unwound by the magnetic powder brake, and after being aligned and centered, they are stacked into the first pair of heated rollers with a roller diameter of 280-320mm. The temperature is raised to 105-115℃, the linear pressure is 0.2-0.4MPa, and the linear speed is 2-4m / min. The composite is completed, and the composite surface material is obtained.

[0009] Step S2: Place the composite material in an intermittent hot-pressing unit, add a mesh strip, maintain a roller temperature of 105-110℃, a linear pressure of 0.3-0.5MPa, a bonding spacing of 50-70cm, and a bonding length of 20-30cm. After bonding, place it in a cooling roller assembly, maintain a roller temperature of 10-20℃, and cool the material to 30-40℃. After trimming the edges to a width of 1.5m, roll it up to obtain the composite material.

[0010] The base fabric is prepared by the following method: polyester filament is activated by atmospheric pressure low temperature plasma, then co-extruded with thermoplastic polyurethane and low melting point copolyester, and then woven.

[0011] The lining is prepared by the following method: keratin extracted from waste feathers is grafted onto modified lyocell short fibers to form a fiber web, which is then sprayed with a crosslinking solution and hot-pressed with pure cotton spunlace fabric.

[0012] The mesh strip is made by wrapping ultra-high strength polyethylene filament with nylon 6 outer yarn, untwisting treatment, and then impregnating and coating with a mixed emulsion.

[0013] Preferably, the preparation steps of the base fabric in step S1 are as follows:

[0014] Step A1: Place the polyester filament in a low-temperature plasma treatment machine under normal pressure, introduce air at a flow rate of 15-25L / min, power of 150-250W, frequency of 35-45Hz, and a treatment speed of 4-6m / min. After the treatment is completed, activated polyester filament is obtained.

[0015] Step A2: Add thermoplastic polyurethane granules and low-melting-point copolyester chips into a twin-screw extruder. The temperature of zone 1 is 150-170℃, zone 2 is 180-190℃, zone 3 is 195-205℃, the die temperature is 190-200℃, the screw speed is 160-200 rpm, hold for 2-4 minutes, cool down to 10-20℃, vacuum dry, and obtain skin granules with a particle size of 3mm.

[0016] Step A3: The activated polyester filament is wound onto the unwinding frame and pre-tensioned to 15-25N. The cortex particles are placed in a single-screw extruder with a feed temperature of 170-190℃, a compression temperature of 195-205℃, a metering temperature of 205-215℃, a die temperature of 205-215℃, a rotation speed of 15-25rpm, and a back pressure of 4-6MPa. The activated polyester filament and cortex melt are combined at the die outlet and cooled by air at 20-30℃ with a wind speed of 0.3-0.8m / s. The mixture is then placed on a rapier loom with a warp density of 35-45 yarns / cm and a weft density of 25-35 yarns / cm to obtain the base fabric.

[0017] Preferably, the mass ratio of the thermoplastic polyurethane particles to the low-melting-point copolyester chips in step A2 is 1.4-1.6:1.

[0018] Preferably, the preparation steps of the lining material in step S2 are as follows:

[0019] Step B1: Feed the keratin-modified short fibers into the coarse opening machine, using a pin beater at a speed of 550-650 rpm. Then, place them in the fine opening machine, using a carding needle beater at a speed of 850-950 rpm. Finally, feed them into the air-laid web forming machine, with a web speed of 2-4 m / min and a mass of 75-85 g / m. 3 A fiber web with a thickness of 15-20mm is obtained;

[0020] Step B2: Place the pure cotton spunlace fabric on unwinding frame a and unwinding frame b respectively, with a tension of 6-10N, and bond the upper and lower surfaces of the fiber web. Pre-press with guide rollers at a linear pressure of 0.08-0.12MPa. Spray crosslinking liquid at a spray pressure of 0.5-0.7MPa, a running speed of 2-3m / min, and a spray flow rate of 250-350mL / min. After spraying, place it in a constant temperature flat plate hot press, heat it to 60-70℃, press it to a pressure of 0.2-0.4MPa, and hold it under pressure for 2-4 minutes. After holding the pressure, cool it to 20-30℃ to obtain the lining.

[0021] Preferably, the preparation steps of the keratin-modified short fibers in step B1 are as follows:

[0022] Step C1: Add urea to deionized water at 20-30℃ and 60-100 rpm for 30-40 minutes. Add L-cysteine ​​and stir for 20-30 minutes. Once stirring is complete, the extract is obtained.

[0023] Step C2: Add feather powder to the extraction solution, stir at 40-50 rpm, add 4 mol / L sodium hydroxide solution, adjust the pH to 9.3-9.7, heat to 65-75℃, increase the stirring speed to 90-110 rpm, keep warm and stir for 3.5-4.5 hours. After the heat preservation is complete, cool down to 30-40℃, pass through a 200-mesh sieve to obtain keratin stock solution;

[0024] Step C3: Add lyocell short fibers to the keratin stock solution, stir at 30-40 rpm, add crosslinking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir for 10-20 min, heat to 35-45℃, stir for 100-140 min until the reaction is complete, wash with deionized water, dry to obtain keratin modified short fibers.

[0025] Preferably, the mass ratio of urea, L-cysteine ​​and deionized water in step C1 is 0.76-0.80:0.038-0.042:1;

[0026] The mass ratio of feather powder to extract in step C2 is 0.4-0.6:1;

[0027] In step C3, the mass ratio of short fibers, keratin solution and crosslinking agent is 0.064-0.068:1:0.0012-0.0014.

[0028] Preferably, the preparation steps of the mesh strip in step S2 are as follows:

[0029] Step D1: Pass the ultra-high strength polyethylene filament through the guide, magnetic powder brake, and tension sensor, then through the center hole of the hollow spindle, and into the exit roller nip. The pretension is 15-25 cN. Place the nylon 6 outer yarn bobbin on the rotary spindle. The spindle speed is 5000-7000 rpm, the wrapping twist is 750-850 twists / m, the first round yarn exit speed is 7-8 m / min, and an untwisting device is installed at the exit roller. The second round yarn exit speed is 7.5-8.5 m / min, and the untwisting is 550-750 twists. Place it on a high-speed shuttleless braiding machine, and install the wrapped and untwisted yarn bobbin on the warp frame. The warp density is 3-4 yarns / cm, the weft density is 3-4 yarns / cm, and the yarn tension is 13-15 N, resulting in a fabric strip roll.

[0030] Step D2: Using a doctor blade dip coating machine, immerse the fabric strip roll into the mixed emulsion at a speed of 1.5-2.5 m / min and a gap of 0.53-0.55 mm between the doctor blade and the surface of the dip roller. After coating, dry with hot air and cool to 20-30℃ to obtain a mesh fabric strip.

[0031] Preferably, the preparation steps of the mixed emulsion in step D2 are as follows:

[0032] Step E1: Add octamethylcyclotetrasiloxane, end-capping agent terminal hydroxyl silicone oil oligomer, and emulsifier hexadecyltrimethylammonium bromide to deionized water, stir at 3000-5000 rpm for 30-40 min, heat to 75-85℃, reduce the stirring speed to 150-250 rpm, add catalyst potassium hydroxide, react for 4-6 h, after the reaction is complete, cool to 40-50℃, add dilute acetic acid, adjust the pH to 6.8-7.0, pass through a 200-mesh sieve to obtain organosilicon modified emulsion;

[0033] Step E2: Add the silicone-modified emulsion to the waterborne polyurethane emulsion, stir at 250-350 rpm for 15-25 minutes, add the thickener, stir for 30-40 minutes, and obtain a mixed emulsion with a viscosity of 4700-5300 mPa·s.

[0034] Preferably, the mass ratio of octamethylcyclotetrasiloxane, end-capping agent, emulsifier, deionized water and catalyst in step E1 is 1:0.03-0.005:0.08-0.12:2.2-2.5:0.001-0.002.

[0035] Preferably, the mass ratio of the organosilicon-modified emulsion, the waterborne polyurethane emulsion, and the thickener in step E2 is 0.16-0.18:1:0.008-0.012.

[0036] The beneficial effects of this invention are:

[0037] 1. This invention achieves efficient interfacial bonding between the base fabric fiber and the skin material by activating polyester filament with high-pressure low-temperature plasma and combining it with a thermoplastic polyurethane and a low-melting-point copolyester co-extruded skin without the need for external adhesives. This significantly improves the interlayer peel strength of the composite material while avoiding organic solvent residues, thus meeting the safety and environmental protection requirements for close-fitting fashion wear.

[0038] 2. This invention uses keratin-modified short fibers and pure cotton spunlace fabric to construct the lining. Keratin is extracted from waste feather powder and grafted onto lyocell fibers, giving the lining good biodegradability and skin-friendly moisture absorption. At the same time, through airflow web forming and hot pressing shaping processes, the lining has a suitable stiffness-flexibility gradient, providing effective support for specific areas of the garment while maintaining overall softness and drape.

[0039] 3. This invention intermittently heat-presses ultra-high strength polyethylene / nylon 6 wrapped untwisted mesh strips into the composite material, and combines this with silicone-modified waterborne polyurethane emulsion impregnation treatment, so that the mesh strips have high tensile strength and fatigue resistance, and the bonding spacing and length are adjustable. This achieves localized differentiated reinforcement of stress-bearing parts such as shoulders and plackets, effectively solving the problem that traditional homogeneous adhesive layers lead to inconsistent stiffness, structural stability and wearing comfort.

[0040] 4. This invention adopts a water-based emulsion system and a hot rolling-hot pressing composite process without hot melt adhesive film throughout the entire process, avoiding the use of organic solvents and formaldehyde crosslinking agents. The resulting composite material has low VOC release characteristics, and the keratin modified fiber and pure cotton spunlace fabric components can be naturally degraded, which meets the urgent needs of the fashion industry to develop towards green, low-carbon and circular recycling.

[0041] 5. This invention achieves stable interfacial fusion bonding and physical anchoring of the base fabric, lining, and mesh strips by precisely controlling the temperature, linear pressure, speed, and cooling and shaping parameters of each process. The composite material maintains excellent dimensional stability and shape retention even after repeated wear and washing, and has a soft and flexible feel and good breathability. It is widely applicable to the structural lining, local reinforcement, and decorative composite fabric fields of high-end fashion. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0043] Example 1: Preparation of a mixed emulsion:

[0044] S1: Add 1000g of octamethylcyclotetrasiloxane, 30g of end-capping agent hydroxyl-terminated silicone oil oligomer and 80g of emulsifier hexadecyltrimethylammonium bromide to 2200g of deionized water, stir at 3000rpm for 40min, heat to 75℃, reduce the stirring speed to 250rpm, add 1g of catalyst potassium hydroxide, react for 4h, the reaction is complete, cool to 50℃, add dilute acetic acid, adjust the pH to 6.8-7.0, pass through a 200-mesh sieve to obtain organosilicon modified emulsion;

[0045] S2: Add 160g of silicone-modified emulsion to 1000g of waterborne polyurethane emulsion, stir at 250rpm for 25min, add 8g of thickener, stir for 30min, and the viscosity is 4700mPa·s to obtain a mixed emulsion.

[0046] Example 2: Preparation of a mixed emulsion:

[0047] S1: Add 1000g of octamethylcyclotetrasiloxane, 40g of end-capping agent hydroxyl-terminated silicone oil oligomer and 100g of emulsifier hexadecyltrimethylammonium bromide to 2350g of deionized water, stir at 4000rpm for 35min, heat to 80℃, reduce the stirring speed to 200rpm, add 1.5g of catalyst potassium hydroxide, react for 5h, after the reaction is complete, cool to 45℃, add dilute acetic acid, adjust the pH to 6.8-7.0, pass through a 200-mesh sieve to obtain organosilicon modified emulsion;

[0048] S2: Add 170g of silicone-modified emulsion to 1000g of waterborne polyurethane emulsion, stir at 300rpm for 20min, add 10g of thickener, stir for 35min, and obtain a mixed emulsion with a viscosity of 5000mPa·s.

[0049] Example 3: Preparation of a mixed emulsion:

[0050] S1: Add 1000g of octamethylcyclotetrasiloxane, 50g of end-capping agent hydroxyl-terminated silicone oil oligomer and 120g of emulsifier hexadecyltrimethylammonium bromide to 2500g of deionized water, stir at 5000rpm for 30min, heat to 85℃, reduce the stirring speed to 150rpm, add 2g of catalyst potassium hydroxide, react for 6h, the reaction is complete, cool to 40℃, add dilute acetic acid, adjust the pH to 6.8-7.0, pass through a 200-mesh sieve to obtain organosilicon modified emulsion;

[0051] S2: Add 180g of silicone-modified emulsion to 1000g of waterborne polyurethane emulsion, stir at 350rpm for 15min, add 12g of thickener, stir for 40min, the viscosity is 5300mPa·s, and a mixed emulsion is obtained.

[0052] Example 4: Preparation of a mesh fabric strip

[0053] S1: The ultra-high strength polyethylene filament is guided through the guide, magnetic powder brake, and tension sensor, and then through the center hole of the hollow spindle to the exit roller nip. The pretension is 15cN. The nylon 6 outer yarn bobbin is placed on the rotary spindle at a spindle speed of 7000rpm and a wrapping twist of 750 twists / m. The first round of yarn exit speed is 8m / min. An untwisting device is installed at the exit roller. The second round of yarn exit speed is 7.5m / min and the untwisting is 750 twists. The yarn is placed on a high-speed shuttleless weaving machine. The wrapped and untwisted yarn bobbin is installed on the warp frame with a warp density of 3 yarns / cm, a weft density of 4 yarns / cm, and a yarn tension of 13N to obtain a fabric strip roll.

[0054] S2: Using a doctor blade dip coating machine, the strip roll is dipped into the mixed emulsion (Example 1) at a running speed of 1.5m / min and a gap of 0.55mm between the doctor blade and the surface of the dip roller. After coating is completed, it is dried with hot air and cooled to 20°C to obtain a mesh strip.

[0055] Example 5: Preparation of a mesh fabric strip

[0056] S1: The ultra-high strength polyethylene filament is guided through the yarn guide, magnetic powder brake, and tension sensor, and then introduced into the exit roller nip through the center hole of the hollow spindle. The pretension is 20cN. The nylon 6 outer yarn bobbin is placed on the rotary spindle with a spindle speed of 6000rpm and a wrapping twist of 800 twists / m. The first round yarn exit speed is 7.5m / min. An untwisting device is installed at the exit roller. The second round yarn exit speed is 8m / min and the untwisting twist is 650 twists. The yarn is placed on a high-speed shuttleless weaving machine. The wrapped and untwisted yarn bobbin is installed on the warp frame with a warp density of 3.5 yarns / cm, a weft density of 3.5 yarns / cm, and a yarn tension of 14N to obtain a fabric strip roll.

[0057] S2: Using a doctor blade dip coating machine, the strip roll is immersed in the mixed emulsion (Example 2) at a running speed of 2m / min. The gap between the doctor blade and the surface of the dip roller is 0.54mm. After coating is completed, it is dried with hot air and cooled to 25°C to obtain a mesh strip.

[0058] Example 6: Preparation of a mesh fabric strip

[0059] S1: The ultra-high strength polyethylene filament is passed through the guide, magnetic powder brake, and tension sensor, and then through the center hole of the hollow spindle to the exit roller nip. The pretension is 25cN. The nylon 6 outer yarn bobbin is placed on the rotary spindle. The spindle speed is 5000rpm, the wrapping twist is 850 twists / m, the first round yarn exit speed is 7m / min, and an untwisting device is installed at the exit roller. The second round yarn exit speed is 8.5m / min, and the untwisting is 550 twists. It is placed on a high-speed shuttleless braiding machine. The wrapped and untwisted yarn bobbin is installed on the warp frame. The warp density is 4 yarns / cm, the weft density is 3 yarns / cm, and the yarn tension is 15N, resulting in a fabric strip roll.

[0060] S2: Using a doctor blade dip coating machine, the strip roll is immersed in the mixed emulsion (Example 3) at a running speed of 2.5m / min and a gap of 0.53mm between the doctor blade and the surface of the dip roller. After coating is completed, it is dried with hot air and cooled to 30°C to obtain a mesh strip.

[0061] Example 7: Preparation of a keratin-modified short fiber

[0062] S1: Add 760g of urea to 1000g of deionized water at 20℃ and 100rpm for 30min. Add 42g of L-cysteine ​​and stir for 30min. Once stirring is complete, the extract is obtained.

[0063] S2: Add 400g of feather powder to 1000g of extract, stir at 40rpm, add 4mol / L sodium hydroxide solution, adjust the pH to 9.3-9.7, heat to 75℃, increase the stirring speed to 90rpm, keep warm and stir for 4.5h, after the heat preservation is complete, cool down to 30℃, pass through a 200-mesh sieve to obtain keratin stock solution;

[0064] S3: Add 64g of lyocell short fibers to 1000g of keratin stock solution, stir at 30rpm, add 1.2g of crosslinking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir for 20min, heat to 35℃, stir for 140min, after the reaction is complete, wash with deionized water, dry, and obtain keratin modified short fibers.

[0065] Example 8: Preparation of a keratin-modified short fiber

[0066] S1: Add 780g of urea to 1000g of deionized water at 25℃ and 80rpm for 35min. Add 40g of L-cysteine ​​and stir for 25min. Once stirring is complete, the extract is obtained.

[0067] S2: Add 500g of feather powder to 1000g of extract, stir at 45rpm, add 4mol / L sodium hydroxide solution, adjust pH to 9.3-9.7, heat to 70℃, increase stirring speed to 100rpm, keep warm and stir for 4h, after the heat preservation is complete, cool to 35℃, pass through a 200-mesh sieve to obtain keratin stock solution.

[0068] S3: Add 66g of lyocell short fibers to 1000g of keratin stock solution, stir at 35rpm, add 1.3g of crosslinking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir for 15min, heat to 40℃, stir for 120min, after the reaction is complete, wash with deionized water, dry, and obtain keratin modified short fibers.

[0069] Example 9: Preparation of a keratin-modified short fiber

[0070] S1: Add 800g of urea to 1000g of deionized water at 30℃ and 60rpm for 40min. Add 42g of L-cysteine ​​and stir for 20min. Once stirring is complete, the extract is obtained.

[0071] S2: Add 600g of feather powder to 1000g of extract, stir at 50rpm, add 4mol / L sodium hydroxide solution, adjust the pH to 9.3-9.7, heat to 65℃, increase the stirring speed to 110rpm, keep warm and stir for 3.5h, after the heat preservation is complete, cool down to 40℃, pass through a 200-mesh sieve to obtain keratin stock solution;

[0072] S3: Add 68g of lyocell short fibers to 1000g of keratin stock solution, stir at 40rpm, add 1.4g of crosslinking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir for 10min, heat to 45℃, stir for 100min, after the reaction is complete, wash with deionized water, dry, and obtain keratin modified short fibers.

[0073] Example 10: Preparation of a Lining Material

[0074] S1: Keratin-modified short fibers (Example 7) are fed into a coarse opening machine, using a pin beater at a speed of 550 rpm. Then, they are placed in a fine opening machine, using a carding needle beater at a speed of 950 rpm. Finally, they enter an air-laid web forming machine, with a web speed of 2 m / min and a mass of 85 g / m. 3 A fiber web with a thickness of 15mm is obtained;

[0075] S2: Place the pure cotton spunlace fabric on unwinding frame a and unwinding frame b respectively, with a tension of 10N, and bond the upper and lower surfaces of the fiber web. Pre-press with guide rollers, linear pressure of 0.08MPa, spray crosslinking liquid, spray pressure of 0.7MPa, running speed of 2m / min, spray flow rate of 350mL / min. After spraying, place it in a constant temperature platen hot press, heat to 60℃, pressure of 0.4MPa, hold pressure for 2min, after holding pressure, cool to 30℃ to obtain the lining.

[0076] Example 11: Preparation of a Lining Material

[0077] S1: Keratin-modified short fibers (Example 8) are fed into a coarse opening machine, using a pin beater at 600 rpm. Then, they are placed in a fine opening machine, using a carding needle beater at 900 rpm, and finally fed into an air-flow web forming machine at a web speed of 3 m / min and a mass of 80 g / m. 3 A fiber web with a thickness of 18mm was obtained.

[0078] S2: Place the pure cotton spunlace fabric on unwinding frame a and unwinding frame b respectively, with a tension of 8N, and bond the upper and lower surfaces of the fiber web. Pre-press with guide rollers, linear pressure of 0.1MPa, spray crosslinking liquid, spray pressure of 0.6MPa, running speed of 2.5m / min, spray flow rate of 300mL / min. After spraying, place it in a constant temperature platen hot press, heat to 65℃, pressure of 0.3MPa, hold pressure for 3min, after holding pressure, cool to 25℃ to obtain the lining.

[0079] Example 12: Preparation of a Lining Material

[0080] S1: Keratin-modified short fibers (Example 9) are fed into a coarse opening machine, using a pin beater at 650 rpm. Then, they are placed in a fine opening machine, using a carding needle beater at 850 rpm. Finally, they enter an air-laid web forming machine at a web speed of 4 m / min and a mass of 75 g / m. 3 A fiber web with a thickness of 20mm is obtained;

[0081] S2: Place the pure cotton spunlace fabric on unwinding frame a and unwinding frame b respectively, with a tension of 6N, and bond the upper and lower surfaces of the fiber web. Pre-press with guide rollers, linear pressure of 0.12MPa, spray crosslinking liquid, spray pressure of 0.5MPa, running speed of 3m / min, spray flow rate of 250mL / min. After spraying, place it in a constant temperature platen hot press, heat to 70℃, pressure of 0.2MPa, hold pressure for 4min, after holding pressure, cool to 30℃ to obtain the lining.

[0082] Example 13: Preparation of a base fabric

[0083] S1: Place the polyester filament in a low-temperature plasma treatment machine under normal pressure, introduce air at a flow rate of 15L / min, power of 250W, frequency of 35Hz, and a treatment speed of 6m / min. After the treatment is completed, activated polyester filament is obtained.

[0084] S2: Thermoplastic polyurethane granules and low-melting-point copolyester chips are added to a twin-screw extruder. The temperature of zone 1 is 150℃, zone 2 is 190℃, zone 3 is 195℃, the die temperature is 200℃, the screw speed is 160rpm, the temperature is held for 4 minutes, the temperature is lowered to 10℃, and the particles are vacuum dried to a particle size of 3mm to obtain skin granules.

[0085] S3: The activated polyester filament is wound onto the unwinding frame and pre-tensioned to 15N. The cortex particles are placed in a single-screw extruder with a feed temperature of 190℃, a compression temperature of 195℃, a metering temperature of 215℃, a die temperature of 205℃, a rotation speed of 25rpm, and a back pressure of 4MPa. The activated polyester filament and cortex melt are combined at the die outlet and cooled by air at 30℃ with a wind speed of 0.3m / s. The mixture is then placed on a rapier loom with a warp density of 45 yarns / cm and a weft density of 35 yarns / cm to obtain the base fabric.

[0086] Example 14: Preparation of a base fabric

[0087] S1: Place the polyester filament in a low-temperature plasma treatment machine under normal pressure, introduce air at a flow rate of 20L / min, power of 200W, frequency of 40Hz, and a treatment speed of 5m / min. After the treatment is completed, activated polyester filament is obtained.

[0088] S2: Add thermoplastic polyurethane granules and low-melting-point copolyester chips into a twin-screw extruder. The temperature of zone 1 is 160℃, the temperature of zone 2 is 185℃, the temperature of zone 3 is 200℃, the die temperature is 195℃, the screw speed is 180rpm, hold for 3min, cool down to 15℃, vacuum dry, and obtain skin granules with a particle size of 3mm.

[0089] S3: The activated polyester filament is wound onto the unwinding frame and pre-tensioned at 20N. The cortex particles are placed in a single-screw extruder with a feed temperature of 180℃, a compression temperature of 200℃, a metering temperature of 210℃, a die temperature of 210℃, a rotation speed of 20rpm, and a back pressure of 5MPa. The activated polyester filament and cortex melt are combined at the die outlet and cooled by air at 25℃ with a wind speed of 0.5m / s. The mixture is then placed on a rapier loom with a warp density of 40 yarns / cm and a weft density of 30 yarns / cm to obtain the base fabric.

[0090] Example 15: Preparation of a base fabric

[0091] S1: Place the polyester filament in a low-temperature plasma treatment machine under normal pressure, introduce air at a flow rate of 25L / min, power of 150W, frequency of 45Hz, and a treatment speed of 4m / min. After the treatment is completed, activated polyester filament is obtained.

[0092] S2: Add thermoplastic polyurethane granules and low-melting-point copolyester chips into a twin-screw extruder. The temperature of zone 1 is 170℃, the temperature of zone 2 is 180℃, the temperature of zone 3 is 205℃, the die temperature is 190℃, the screw speed is 200rpm, hold for 2min, cool down to 20℃, vacuum dry, and obtain skin granules with a particle size of 3mm.

[0093] S3: The activated polyester filament is wound onto the unwinding frame and pre-tensioned to 25N. The cortex particles are placed in a single-screw extruder with a feed temperature of 170℃, a compression temperature of 205℃, a metering temperature of 205℃, a die temperature of 215℃, a rotation speed of 15rpm, and a back pressure of 6MPa. The activated polyester filament and cortex melt are combined at the die outlet and cooled by 20℃ with an air speed of 0.8m / s. The mixture is then placed on a rapier loom with a warp density of 35 yarns / cm and a weft density of 35 yarns / cm to obtain the base fabric.

[0094] Example 16: A method for preparing a high-performance modified fiber composite material for the fashion industry

[0095] S1: The base fabric (Example 15) and the lining (Example 12) are unwound by a magnetic powder brake, and after being aligned and centered, they are stacked into the first pair of heated rollers with a roller diameter of 300 mm, heated to 110°C, with a linear pressure of 0.3 MPa and a linear speed of 3 m / min. The composite is completed, and the composite surface material is obtained.

[0096] S2: Place the composite material in an intermittent hot-pressing bonding unit, add a mesh strip (Example 4), roller temperature 106℃, linear pressure 0.4MPa, bonding spacing 60cm, bonding length 25cm. After bonding is completed, place it in a cooling roller group, roller temperature 15℃, the material is cooled to 35℃, and after trimming to a width of 1.5m, it is rolled up to obtain the composite material.

[0097] Example 17: A method for preparing a high-performance modified fiber composite material for the fashion industry

[0098] S1: The base fabric (Example 14) and the lining (Example 11) are unwound by a magnetic powder brake, and after being aligned and centered, they are stacked into the first pair of heated rollers with a roller diameter of 300 mm, heated to 108°C, with a linear pressure of 0.3 MPa and a linear speed of 3 m / min. The composite is completed, and the composite surface material is obtained.

[0099] S2: Place the composite material in an intermittent hot-pressing bonding unit, add a mesh strip (Example 5), roller temperature 108℃, linear pressure 0.4MPa, bonding spacing 60cm, bonding length 25cm. After bonding is completed, place it in a cooling roller group, roller temperature 15℃, the material temperature drops to 35℃, and after trimming to a width of 1.5m, it is rolled up to obtain the composite material.

[0100] Example 18: A method for preparing a high-performance modified fiber composite material for the fashion industry

[0101] S1: The base fabric (Example 13) and the lining (Example 10) are unwound by a magnetic powder brake, and after being aligned and centered, they are stacked into the first pair of heated rollers with a roller diameter of 320 mm, heated to 105°C, with a linear pressure of 0.4 MPa and a linear speed of 2 m / min. The composite is completed, and the composite surface material is obtained.

[0102] S2: Place the composite material in an intermittent hot-pressing bonding unit, add a mesh strip (Example 6), roller temperature 110℃, linear pressure 0.3MPa, bonding spacing 70cm, bonding length 20cm. After bonding is completed, place it in a cooling roller group, roller temperature 20℃, the material is cooled to 30℃, and after trimming to a width of 1.5m, it is rolled up to obtain the composite material.

[0103] Comparative Example 1:

[0104] Compared with Example 16, the difference in this comparative example is that the atmospheric pressure low-temperature plasma treatment step in step A1 is omitted in the preparation process of the base fabric described in step S1. The remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, the composite material is obtained.

[0105] Comparative Example 2:

[0106] The difference between this comparative example and Example 16 is that no mesh strips are added in step S2. Instead, the composite material is placed directly on the cooling roller assembly to cool down and then trimmed and rolled up. All other steps and parameters are the same, and will not be repeated here. The final composite material is obtained.

[0107] Comparative Example 3:

[0108] Compared with Example 16, this comparative example only replaces "keratin-modified short fiber" with "lyocell short fiber". All other steps and parameters are the same, and will not be repeated here. The final composite material is obtained.

[0109] Comparative Example 4:

[0110] Compared with Example 16, the difference in this comparative example is that in the preparation process of the base fabric in step S1, the skin particles in step A2 only use thermoplastic polyurethane particles and do not add low-melting-point copolyester chips. The remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, the composite material is obtained.

[0111] Comparative Example 5:

[0112] Compared with Example 16, the difference in this comparative example is that in the preparation process of the mesh strip in step S2, the untwisting device is removed in step D1. That is, after the ultra-high strength polyethylene filament is wrapped with nylon 6, it is not untwisted and is directly woven. The remaining steps and parameters are the same as in Example 16, and will not be repeated in this comparative example. Finally, the composite material is obtained.

[0113] Performance testing:

[0114] interlayer peel strength test

[0115] The universal testing machine was used in accordance with the GB / T 2792-2014 testing standard.

[0116] 1. Take the composite materials of Examples 16-18 and Comparative Examples 1-5 respectively, cut them into strips of 50mm×200mm, and pre-separate the base fabric and the lining layer by about 50mm.

[0117] 2. Clamp the peeled base fabric layer and lining layer separately in the upper and lower fixtures of the universal testing machine, with a fixture spacing of 100 mm. Ensure the peeling angle is 180° and the tensile peeling speed is 100 mm / min. Continuously record the force values ​​during the peeling process. Discard the first and last 20 mm areas and take the average force value of the middle stable area as the interlayer peel strength of the sample, in N / 50 mm. Test 5 parallel samples for each sample and take the arithmetic mean.

[0118] Tensile strength test at break

[0119] The universal testing machine was used in accordance with the GB / T 3923.1-2013 testing standard.

[0120] The composite materials of Examples 16-18 and Comparative Examples 1-5 were taken and cut into strips of 50mm×300mm. The two ends of the sample were clamped flat in the upper and lower clamps of the universal testing machine with a clamp spacing of 200mm. The pre-tension was set to 2N and the tensile speed was 100mm / min. The load was continuously applied until the sample broke. The maximum breaking strength (N) was recorded. Five parallel samples were tested in the warp and weft directions for each sample, and the average value was taken.

[0121] Table 1 Test Results of Examples and Comparative Examples

[0122] project Interlayer peel strength (N / 50mm) Meridional tensile strength at break (N) Tensile strength at break (N) Example 16 18.6 1420 1180 Example 17 18.2 1405 1165 Example 18 17.9 1390 1150 Comparative Example 1 8.7 1350 1120 Comparative Example 2 17.5 1020 850 Comparative Example 3 15.8 1380 1145 Comparative Example 4 9.3 1365 1130 Comparative Example 5 17.2 1180 960

[0123] Sag coefficient test

[0124] The sag tester was used in accordance with the GB / T 18318.1-2009 test standard.

[0125] 1. Take the composite materials of Examples 16-18 and Comparative Examples 1-5 respectively, cut out circular samples with a diameter of 24cm, and mark a positioning hole with a diameter of 1.2cm in the center of the sample.

[0126] 2. Place the sample on the horizontal support plate of the sag tester, release the sample to allow it to hang naturally, and after 1 minute of stillness, record the projected outline of the suspended sample. The instrument will automatically calculate the sag coefficient (%).

[0127] Table 2. Test results of sag coefficient for the examples and comparative examples.

[0128] project Sag coefficient of the reinforced area (%) Sag coefficient of unreinforced area (%) Difference in sag coefficient between reinforced and unreinforced areas (%) Example 16 42.3 38.5 3.8 Example 17 42.8 39.0 3.8 Example 18 43.2 39.3 3.9 Comparative Example 1 43.6 40.0 3.6 Comparative Example 2 40.2 40.0 0.2 Comparative Example 3 46.8 43.5 3.3 Comparative Example 4 43.0 39.2 3.8 Comparative Example 5 51.2 39.1 12.1

[0129] Peel strength retention rate test after water washing

[0130] The universal testing machine was used in accordance with the GB / T 8629-2017 testing standard.

[0131] 1. Take the composite materials of Examples 16-18 and Comparative Examples 1-5 respectively, cut a 50cm×200cm sample, put it into a standard washing machine, add standard detergent, water temperature 40℃, wash for 45 minutes, after washing, air dry naturally, repeat the above washing-drying process a total of 5 times, and test according to the above interlayer peel strength test procedure.

[0132] 2. Calculation formula:

[0133]

[0134] Table 3. Test results of peel strength retention rate after water washing for the examples and comparative examples.

[0135] project Average interlayer peel strength after washing (N / 50mm) Retention rate (%) Example 16 16.4 88.2 Example 17 16.1 88.5 Example 18 15.7 87.7 Comparative Example 1 4.5 51.7 Comparative Example 2 15.5 88.6 Comparative Example 3 14.0 88.6 Comparative Example 4 5.1 54.8 Comparative Example 5 15.3 89.0

[0136] air permeability test

[0137] According to the GB / T 5453-2025 test standard, an air permeability meter was used;

[0138] Samples from Examples 16-18 and Comparative Examples 1-5 were taken respectively and flatly covered on the test head of the air permeability meter. The test head area was 20 cm². 2 The test pressure drop was 100 Pa. After the pressure stabilized, the air permeability (mm / s) was recorded. Each sample was tested 10 times at different locations, and the average value was taken.

[0139] Free formaldehyde content test

[0140] Refer to the testing standard GB / T 2912.1-2009;

[0141] 1. Take 1.0 g of each of the samples from Examples 16-18 and Comparative Examples 1-5, place them in a 250 mL stoppered iodine flask, add 100 mL of deionized water, place in a water bath at 40±2℃ and shake to extract for 1 h, cool to room temperature, filter, and obtain the extract.

[0142] 2. Take 5 mL of filtrate into a colorimetric tube, add 5 mL of acetylacetone solution, shake well, and place in a water bath at 40±2℃ for 30 min to develop color. After cooling, use a UV-Vis spectrophotometer to measure the absorbance at a wavelength of 412 nm and convert it into the free formaldehyde content (mg / kg) in the sample.

[0143] Table 4 Test Results of Examples and Comparative Examples

[0144] project Air permeability (mm / s) Free formaldehyde content (mg / kg) Example 16 385 Not detected Example 17 378 Not detected Example 18 372 Not detected Comparative Example 1 380 Not detected Comparative Example 2 390 Not detected Comparative Example 3 335 Not detected Comparative Example 4 375 Not detected Comparative Example 5 370 Not detected

[0145] Data Analysis:

[0146] As can be seen from Tables 1-4, the composite material prepared by the present invention has excellent interlaminar peel strength, tensile strength at break, water washability, good wearing comfort, and environmental safety.

[0147] In contrast, Comparative Example 1, due to the lack of atmospheric pressure low-temperature plasma activation treatment on the polyester filaments, resulted in a significant reduction in the interfacial bonding strength between the sheath material and the core filaments. The interlayer peel strength was only 8.7 N / 50 mm, and the retention rate after 5 washes was only 51.7%. This is because the surface of the unactivated polyester filaments lacks polar groups, and it can only form a physical coating with the thermoplastic polyurethane elastomer of the sheath without forming chemical bonds such as hydrogen bonds. Under hydrothermal and peeling forces, interfacial slippage is likely to occur. At the same time, water molecules penetrate along the interfacial defects, further accelerating the bonding failure. In addition, the weak interfacial bonding also caused micro-cracks to appear in the sheath of the base fabric during repeated bending, affecting the wrinkle resistance and durability of the fabric.

[0148] In contrast, Comparative Example 2, due to the lack of intermittent hot-pressing of reinforcing mesh strips into the composite material, resulted in warp and weft tensile strengths of only 1020N and 850N respectively, and a sag coefficient difference of only 0.2% between the reinforced and unreinforced areas. This was because the ultra-high molecular weight polyethylene core filaments in the mesh strips bore the main tensile load, and the resin coating carried by the nylon fleece formed a strong bond with the lining under hot pressing. Without this structure, there was no local stiffness enhancement in the stressed areas. At the same time, the mechanical properties of the unreinforced and reinforced areas tended to be the same, making it impossible to achieve a differentiated reinforcement effect. In addition, stress-concentrated areas such as the shoulders and plackets of the garment were prone to plastic deformation during wear, significantly shortening the shape retention life.

[0149] In contrast, in Comparative Example 3, replacing keratin-modified short fibers with ordinary lyocell short fibers resulted in an increase in the drape coefficients of the reinforced and unreinforced areas to 46.8% and 43.5%, respectively, and a decrease in breathability to 335 mm / s. The fabric also became stiffer and more stuffy to wear. This is because keratin grafting gives the fibers a natural microporous structure and the unique flexible segments of proteins, while ordinary lyocell fibers have a smooth and dense surface and high bending stiffness. At the same time, they lack the additional hydrogen bond cross-linking sites between keratin molecular chains and calcium alginate networks, resulting in an increase in the overall rigidity of the lining and a decrease in its resilience. In addition, the biodegradability and natural silky texture of the keratin-modified fibers are also lost, failing to meet the dual ecological and aesthetic requirements of high-end fashion.

[0150] In contrast, Comparative Example 4, which used only thermoplastic polyurethane for the skin granules without adding low-melting-point copolyester chips, resulted in an interlayer peel strength of only 9.3 N / 50 mm and a retention rate of only 54.8% after 5 washes. This is because the low-melting-point copolyester melts and flows at a hot-rolling composite temperature of 112°C, which can fill the microscopic voids at the interface between the surface layer and the lining and form mechanical anchoring points. In contrast, the pure thermoplastic polyurethane elastomer only softens and does not melt at this temperature, lacking wetting and spreading ability. At the same time, it fails to form a microphase separation interface structure, resulting in the bonding force between the surface layer and the lining being heavily dependent on physical adhesion. In addition, the absence of low-melting-point components in the melt bonding process also leads to interface embrittlement of the composite material during low-temperature washing, further deteriorating its durability.

[0151] In Comparative Example 5, the absence of the untwisting device during the fabric preparation process resulted in a sag coefficient of 51.2% in the reinforced area, a difference of 12.1% compared to the non-reinforced area. In contrast, the difference in the Example was only 3.8-3.9%. This is because, when untwisted, the nylon outer yarn is tightly attached to the ultra-high molecular weight polyethylene core yarn, and the overall wrapped yarn is in a high-rigidity rod shape. The bending modulus is much greater than that of the fluffy untwisted structure in the Example. At the same time, a severe stiffness gradient is formed between the reinforced and non-reinforced areas. In addition, the core yarn and the outer yarn of the untwisted yarn are bent simultaneously. The ultra-high molecular weight polyethylene core yarn is prone to irreversible bending deformation during repeated flexing, which reduces the fatigue life of the reinforced area.

[0152] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

[0153] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A method for preparing a high-performance modified fiber composite material for the fashion industry, characterized in that, The specific steps of the preparation method are as follows: Step S1: The base fabric and the lining are unwound by the magnetic powder brake, and after being aligned and centered, they are stacked into the first pair of heated rollers with a roller diameter of 280-320mm. The temperature is raised to 105-115℃, the linear pressure is 0.2-0.4MPa, and the linear speed is 2-4m / min. The composite is completed, and the composite surface material is obtained. Step S2: Place the composite material in an intermittent hot-pressing unit, add a mesh strip, maintain a roller temperature of 105-110℃, a linear pressure of 0.3-0.5MPa, a bonding spacing of 50-70cm, and a bonding length of 20-30cm. After bonding, place it in a cooling roller assembly, maintain a roller temperature of 10-20℃, and cool the material to 30-40℃. After trimming the edges to a width of 1.5m, roll it up to obtain the composite material. The base fabric is prepared by the following method: polyester filament is activated by atmospheric pressure low temperature plasma, then co-extruded with thermoplastic polyurethane and low melting point copolyester, and then woven. The lining is prepared by the following method: keratin extracted from waste feathers is grafted onto modified lyocell short fibers to form a fiber web, which is then sprayed with a crosslinking solution and hot-pressed with pure cotton spunlace fabric. The mesh strip is made by wrapping ultra-high strength polyethylene filament with nylon 6 outer yarn, untwisting treatment, and then impregnating and coating with a mixed emulsion.

2. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 1, characterized in that, The preparation steps of the base fabric in step S1 are as follows: Step A1: Place the polyester filament in a low-temperature plasma treatment machine under normal pressure, introduce air at a flow rate of 15-25L / min, power of 150-250W, frequency of 35-45Hz, and a treatment speed of 4-6m / min. After the treatment is completed, activated polyester filament is obtained. Step A2: Add thermoplastic polyurethane granules and low-melting-point copolyester chips into a twin-screw extruder. The temperature of zone 1 is 150-170℃, zone 2 is 180-190℃, zone 3 is 195-205℃, the die temperature is 190-200℃, the screw speed is 160-200 rpm, hold for 2-4 minutes, cool down to 10-20℃, vacuum dry, and obtain skin granules with a particle size of 3mm. Step A3: The activated polyester filament is wound onto the unwinding frame and pre-tensioned to 15-25N. The cortex particles are placed in a single-screw extruder with a feed temperature of 170-190℃, a compression temperature of 195-205℃, a metering temperature of 205-215℃, a die temperature of 205-215℃, a rotation speed of 15-25rpm, and a back pressure of 4-6MPa. The activated polyester filament and cortex melt are combined at the die outlet and cooled by air at 20-30℃ with a wind speed of 0.3-0.8m / s. The mixture is then placed on a rapier loom with a warp density of 35-45 yarns / cm and a weft density of 25-35 yarns / cm to obtain the base fabric.

3. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 2, characterized in that, The mass ratio of thermoplastic polyurethane particles to low-melting-point copolyester chips in step A2 is 1.4-1.6:

1.

4. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 1, characterized in that, The preparation steps of the lining material in step S2 are as follows: Step B1: Feed the keratin-modified short fibers into the coarse opening machine, using a pin beater at a speed of 550-650 rpm. Then, place them in the fine opening machine, using a carding needle beater at a speed of 850-950 rpm. Finally, feed them into the air-laid web forming machine, with a web speed of 2-4 m / min and a mass of 75-85 g / m. 3 A fiber web with a thickness of 15-20mm is obtained; Step B2: Place the pure cotton spunlace fabric on unwinding frame a and unwinding frame b respectively, with a tension of 6-10N, and bond the upper and lower surfaces of the fiber web. Pre-press with guide rollers at a linear pressure of 0.08-0.12MPa. Spray crosslinking liquid at a spray pressure of 0.5-0.7MPa, a running speed of 2-3m / min, and a spray flow rate of 250-350mL / min. After spraying, place it in a constant temperature flat plate hot press, heat it to 60-70℃, press it to a pressure of 0.2-0.4MPa, and hold it under pressure for 2-4 minutes. After holding the pressure, cool it to 20-30℃ to obtain the lining.

5. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 4, characterized in that, The preparation steps of the keratin-modified short fibers described in step B1 are as follows: Step C1: Add urea to deionized water at 20-30℃ and 60-100 rpm for 30-40 minutes. Add L-cysteine ​​and stir for 20-30 minutes. Once stirring is complete, the extract is obtained. Step C2: Add feather powder to the extraction solution, stir at 40-50 rpm, add 4 mol / L sodium hydroxide solution, adjust the pH to 9.3-9.7, heat to 65-75℃, increase the stirring speed to 90-110 rpm, keep warm and stir for 3.5-4.5 hours. After the heat preservation is complete, cool down to 30-40℃, pass through a 200-mesh sieve to obtain keratin stock solution; Step C3: Add lyocell short fibers to the keratin stock solution, stir at 30-40 rpm, add crosslinking agent 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, stir for 10-20 min, heat to 35-45℃, stir for 100-140 min until the reaction is complete, wash with deionized water, dry to obtain keratin modified short fibers.

6. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 5, characterized in that, The mass ratio of urea, L-cysteine, and deionized water in step C1 is 0.76-0.80:0.038-0.042:1; The mass ratio of feather powder to extract in step C2 is 0.4-0.6:1; In step C3, the mass ratio of lyocell short fibers, keratin solution and crosslinking agent is 0.064-0.068:1:0.0012-0.0014.

7. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 1, characterized in that, The preparation steps of the mesh strip in step S2 are as follows: Step D1: Pass the ultra-high strength polyethylene filament through the guide, magnetic powder brake, and tension sensor, then through the center hole of the hollow spindle, and into the exit roller nip. The pretension is 15-25 cN. Place the nylon 6 outer yarn bobbin on the rotary spindle. The spindle speed is 5000-7000 rpm, the wrapping twist is 750-850 twists / m, the first round yarn exit speed is 7-8 m / min, and an untwisting device is installed at the exit roller. The second round yarn exit speed is 7.5-8.5 m / min, and the untwisting is 550-750 twists. Place it on a high-speed shuttleless braiding machine, and install the wrapped and untwisted yarn bobbin on the warp frame. The warp density is 3-4 yarns / cm, the weft density is 3-4 yarns / cm, and the yarn tension is 13-15 N, resulting in a fabric strip roll. Step D2: Using a doctor blade dip coating machine, immerse the fabric strip roll into the mixed emulsion at a speed of 1.5-2.5 m / min and a gap of 0.53-0.55 mm between the doctor blade and the surface of the dip roller. After coating, dry with hot air and cool to 20-30℃ to obtain a mesh fabric strip.

8. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 7, characterized in that, The preparation steps of the mixed emulsion in step D2 are as follows: Step E1: Add octamethylcyclotetrasiloxane, end-capping agent terminal hydroxyl silicone oil oligomer, and emulsifier hexadecyltrimethylammonium bromide to deionized water, stir at 3000-5000 rpm for 30-40 min, heat to 75-85℃, reduce the stirring speed to 150-250 rpm, add catalyst potassium hydroxide, react for 4-6 h, after the reaction is complete, cool to 40-50℃, add dilute acetic acid, adjust the pH to 6.8-7.0, pass through a 200-mesh sieve to obtain organosilicon modified emulsion; Step E2: Add the silicone-modified emulsion to the waterborne polyurethane emulsion, stir at 250-350 rpm for 15-25 minutes, add the thickener, stir for 30-40 minutes, and obtain a mixed emulsion with a viscosity of 4700-5300 mPa·s.

9. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 8, characterized in that, In step E1, the mass ratio of octamethylcyclotetrasiloxane, end-capping agent, emulsifier, deionized water and catalyst is 1:0.03-0.005:0.08-0.12:2.2-2.5:0.001-0.

002.

10. The method for preparing a high-performance modified fiber composite material for the fashion industry according to claim 8, characterized in that, The mass ratio of the silicone-modified emulsion, the waterborne polyurethane emulsion, and the thickener in step E2 is 0.16-0.18:1:0.008-0.012.